Fast generations of entangled states between a transmon qubit and microwave photons via shortcuts to adiabaticity. (16th October 2018) - Yan, Run-Ying; Feng, Zhi-Bo; Zhang, Chun-Li; Li, M; Lu, Xiao-Jing; Zhou, Yun-Qing
Abstract: We propose an efficient protocol for rapidly generating quantum entangled states between a transmon qubit and microwave photons via shortcuts to adiabaticity. For a dispersive coupling between the qubit and cavity mode, three composite qubit-photon states constitute our system. Two microwave drivings are applied to the three-level system, leading to a Λ-type interaction. Based on shortcut-like quantum state transfer, the maximally entangled states can be controllably generated in a non-adiabatic manner. We address the dependence of the needed time for generating entangled states on the Rabi couplings, and further analyse the robustness of quantum operations. The present scheme opens up an opportunity for fast creating entangled states of the superconducting qubit-cavity systems.